Stationary axially symmetric Brans-Dicke-Maxwell fields - Singh T.; Rai L.N. (My University, 2025)
A method is presented which enables one to obtain solutions to the stationary axially symmetric Brans-Dicke fields coupled to source-free Maxwell fields from the solutions of the Einstein-Maxwell equations in Einstein's theory. The Brans-Dicke analog of the Kerr-Newman solution has been obtained as an example. © 1979 Plenum Publishing Corporation.